Sinonasal Osteosarcoma: Report of 14 New Cases and Systematic Review of the Literature - Low, Christopher M.; Gruszczynski, Nelson R.; Moore, Eric J.; Price, Daniel L.; Janus, Jeffrey R.; Kasperbauer, Jan L.; Van Abel, Kathryn M.; Stokken, Janalee K.; Van Gompel, Jamie J.; Link, Michael J.; Choby, Garret (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The objective of this study is to describe the clinical presentation, tumor characteristics, natural history, and treatment patterns of sinonasal osteosarcoma.Methods Fourteen patients who had been treated for osteosarcoma of the nasal cavity and paranasal sinuses at a tertiary care center were reviewed. In addition, a systematic review of the literature for osteosarcoma of the sinonasal cavity was performed.Results In a systematic review, including 14 patients from the authors' institution, 53 total studies including 88 patients were assessed. Median follow-up was 18 months (interquartile range: 8–39 months). The most common presenting symptoms were facial mass or swelling (34%), and nasal obstruction (30%). The most common paranasal sinus involved by tumor was the maxillary sinus (64%), followed by the ethmoid sinuses (52%). The orbit (33%), dura (13%) and infratemporal fossa (10%) were the most common sites of local invasion. The majority of patients underwent surgery followed by adjuvant therapy (52.4%). Increasing age was associated with decreased overall survival rate (unit risk ratio [95% confidence interval (CI)] = 1.02 [1.003–1.043]; p = 0.0216) and T4 disease was associated with decreased disease-specific survival rate (hazard ratio [HR] = 2.87; p = 0.0495). The 2- and 5-year overall survival rates were 68 and 40%, respectively, while 2- and 5-year disease-specific survival rates were 71% and 44%, respectively.Conclusion Sinonasal osteosarcomas are uncommon tumors and can pose a significant therapeutic challenge. Increasing age and T4 disease are associated with worse prognosis. This disease usually warrants consultation by a multidisciplinary team and consideration of multimodality therapy.
Keywords: osteogenic sarcoma; osteosarcoma; nasal cavity; paranasal sinuses; sinonasal; EEA; expanded endonasal approach